Hearing Impairment Simulation Model using the standard MPEG-1 Audio Layer III - Uriz, Alejandro José (2010)
The MPEG standard for digital compression for high-fidelity audio provides two implementations of the psychoacoustic model: the Psychoacoustic Model I and the Psychoacoustic Model II. Both of these models are explained in detail in the ISO/IEC 13818-3:1194(E). In this work a model of the auditory system will be obtained with the purpose of simulating several types of hearing impairments. The system is able to simulate several types of auditory problems from curves that represent the Sound Pressure Level as a function of the frequency.